LEAERNING STRATEGIES IN LISTENING USED BY THE FIRST YEAR STUDENTS OF SMA N 1 MOJOLABAN IN 2010/2011 ACADEMIC YEAR - MAYASARI , AGUSTINA (2011)
The research aims at describing the strategies used by the learner in learning listening, and identifying the strength and the weakness of the strategies used by the learner in learning listening. This research is descriptive qualitative research. The researcher collects the data by observing the English class, especially in listening class and conducting an interview with the teacher and some students. The data include syllabus, listening materials, field notes and interview script, and the method of collecting the data are observation, interview, and documents. From the data analysis, the researcher draws conclusion. First, the strategies used by the learner in learning listening are: (1) Top-down and bottom up strategy, (2) Metacognitive strategies. Second, the strength and the weakness of the strategies used by the learner in learning listening. The strength of the strategies are: (1) it can (2) it makes the students easier to understand the topics in listening activity, (3) it can makes teaching listening optimally, and (4) it can control the class effectively. The weaknesses of the strategies are: (1) When the teacher wrote the vocabulary on the white board, it is not suitable in teaching listening, but more suitable in teaching writing, (2) the teacher needs a lot of time when he wrote the vocabularies on the whiteboard, it can make the listening comprehension in post listening, because the time is limited, (4) the teacher and the students can not evaluate the strategy use in listening activity.